Teramnus hookerianus, a heterotypic synonym of T. labialis (Leguminosae: Papilionoideae) - Ranjan, Vinay (Rheedea, 2016)
Teramnus hookerianus A. Sen is relegated here to a heterotypic synonym of T. labialis (L.f.) Spreng.